CONTESTING CALIPHATE: Opposition of Indonesian Fundamentalist Groups to ISIS Caliphate (JOURNAL OF INDONESIAN ISLAM, 2014)
ISIS (Islamic State of Iraq and Syria) which was declared by al-Baghdādī as an Islamic caliphate (dawlah khilāfah) is not necessarily welcomed by Muslim fundamentalists in Indonesia. Hizbut Tahrir Indonesia (HTI) and Majelis Mujahidin Indonesia (MMI), two Muslims fundamentalist organization that struggle for Islamic caliphate, considers ISIS as deviant and invalid. This article aims to discuss the argument surrounding religious foundation of Islamic caliphate as believed al-Baghdādī as ISIS mastermind and the response of Indonesian fundamentalists to it. While all Islamic fundamentalism believes that establishment of Islamic caliphate is a religious obligation, they do not agree how to implement this obligation. ISIS’s al-Baghdādī is on the opinion that Islamic caliphate is to be implemented with all costs, including using violence and military campaign, Indonesian fundamentalists tend to use non-violence and dialogue as their strategy instead.